KOPERASI 高中生的汉字笔顺掌握分析 - Resya Resya; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2022)
In order to further understand the high school students' mastery of stroke order, the author chose Koperasi high school students as the research object. The purpose is to understand and analyze the students' mastery of the steps of writing Chinese characters. For research purposes, the author used tests and questionnaires to collect data. The data collected shows that write errors are the most common. The reason is that there are too many strokes in Chinese characters, and the error rate is 72.24%, which makes it difficult for students to remember. For high school students learning to write Chinese characters, stroke order is a difficult point. Due to the complexity of stroke order, many students made mistakes in writing Chinese characters and the stroke order was reversed. EachChinese character has its own way of writing, but both strokes and stroke order must conform to the stroke order rules of Chinese characters.